Association of intensity-modulated radiation therapy on overall survival for patients with Hodgkin lymphoma. Issue 1 (January 2016) - Parikh, Rahul R.; Grossbard, Michael L.; Harrison, Louis B.; Yahalom, Joachim
Abstract: Purpose: The purpose of this study was to compare outcomes with Hodgkin lymphoma (HL) patients receiving IMRT (intensity-modulated radiation therapy), versus those receiving 2D/3D-CRT (3-dimensional conformal RT) in a large observational cohort. Patients and methods: We evaluated patients diagnosed with stage I–IV HL from 1998 to 2011 from the National Cancer Database (NCDB). The association between IMRT use vs. 2D/3D-CRT, co-variables, and outcome was assessed in a Cox proportional hazards model. Propensity score (PS) matching was performed to balance known confounding factors. Survival was estimated using the Kaplan–Meier method. Results: Of the 76, 672 patients with HL within the NCDB, 12, 393 patients with stage I-IV HL received RT (median dose = 30.6 Gy) and were eligible for this study, and 6013 patients analyzed for overall survival. The cohort had a median follow-up of 6.2 years and median age of 37 years (range: 18–90). The RT modalities used were: 2D/3D-CRT ( n  = 11, 491, 92.7%) or IMRT ( n  = 902, 7.3%). Patients were more likely to receive IMRT if they were of male gender, early stage, no "B" symptoms, and treated at comprehensive cancer programs (all p  < 0.05). During this time period, there was a significant decrease in use of 2D/3D-CRT from 100% to 81.5%, with a subsequent increase in IMRT utilization from 0% to 18.5%. Five-year overall survival for patients receiving 2D/3D-CRT ( n  = 5844) was 89.9% versus 95.2% for those receiving IMRT ( n  = 169; HR = 0.45; 95% CI, 0.23–0.91, p  = 0.02). After PS-matching based on clinicopathologic characteristics, IMRT use remained associated with improved overall survival (HR = 0.40; 95% CI, 0.16–0.97, p  = 0.04). Conclusions: Our study reveals that HL patients receiving modern RT techniques were associated with an improvement in overall survival. This may have been related to patient selection, access to improved staging and management, or improvements in treatment technology. This represents the only study examining survival outcomes of advanced RT modalities, which may be considered on a case-by-case basis for highly selected patients with HL.